2017
DOI: 10.1088/1361-648x/aa89d1
|View full text |Cite
|
Sign up to set email alerts
|

Gutzwiller variational approach to the two-impurity Anderson model for a metallic host at particle-hole symmetry

Abstract: We study Gutzwiller-correlated wave functions as variational ground states for the two-impurity Anderson model (TIAM) at particle-hole symmetry as a function of the impurity separation [Formula: see text]. Our variational state is obtained by applying the Gutzwiller many-particle correlator to a single-particle product state. We determine the optimal single-particle product state fully variationally from an effective non-interacting TIAM that contains a direct electron transfer between the impurities as variat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The Bethe Ansatz provides the impurity-induced magnetization of the system m ii (J BA K , B, T ) at finite temperatures T and finite external fields B, see eq. (19). For small couplings, J K ≪ 1, the impurity-induced susceptibility is exponentially large, see eq.…”
Section: Impurity-induced Magnetizationmentioning
confidence: 97%
“…The Bethe Ansatz provides the impurity-induced magnetization of the system m ii (J BA K , B, T ) at finite temperatures T and finite external fields B, see eq. (19). For small couplings, J K ≪ 1, the impurity-induced susceptibility is exponentially large, see eq.…”
Section: Impurity-induced Magnetizationmentioning
confidence: 97%
“…(E.1) and (E.5) in Ref. [41]. Using Mathematica 42 we find for the semi-elliptic density of states using d 0 = ρ 0 (0) = 4/π and ln(e) = 1…”
Section: A Ground-state Energymentioning
confidence: 87%
“…(E.1) and (E.5) by Linneweber and collaborators. 41 Using Mathematica 42 we find in one dimension using d 0 = ρ 0 (0) = 2/π and ln(e) = 1…”
Section: Limit Of Small Hybridizationmentioning
confidence: 99%
“…In the TIAM, the Kondo coupling J K is related to the ratio of the Coulomb interaction U and the coupling strength Γ 0 . Linneweber et al investigated the TIAM on the threedimensional simple cubic lattice via a Gutzwiller variational approach and found such a QCP at a critical U c provided the impurities are placed on the lattice sites [78]. The authors indicated that their QCP is probably an artifact of the Gutzwiller variational approach: the Gutzwiller trial wave function only includes local correlations on the impurity site while the NRG reveals already for the Kondo problem the extended nature of the correlated singlet [59,60].…”
Section: Afm Rkky Coupling -The Doniach Scenariomentioning
confidence: 99%